Tantangan dan Strategi Implementasi Kebijakan Anti Bullying di Lingkungan Sekolah SMAN 1 Panyipatan - Sulis Anggraeni; Ahmad Suriansyah; Ratna Purwanti (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
The problem of bullying in schools is a crucial issue that threatens the safety and comfort of the learning environment for students. This study aims to describe and analyze the implementation of anti-bullying policies at SMAN 1 Panyipatan in response to Permendikbudristek Number 46 of 2023. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation of the principal, TPPK teachers, students, and school committees. The results of the study show that the school has formed a Violence Prevention and Handling Team (TPPK), conducted socialization, provided an anonymous reporting box, and strengthened the role of BK teachers and communication with parents. However, significant challenges are still encountered, such as low understanding of the policy, minimal technical training, and limited facilities. The conclusion of this study emphasizes the importance of synergy between schools, parents, and the education office in supporting the policy systematically. The implication is that it is necessary to strengthen human resource capacity, regular monitoring, and develop a child-friendly reporting system so that this policy can be implemented effectively and sustainably